Lighed med hensyn til hvad? Komparativ klimapolitik og politisk teori om lighed - Nedergaard, Peter (Politik, 2013)
This article unveils for the rst time the political norms of equality promoted by the EU, China and the US with regard to their respective views on the allocation of CO2 emission reductions. ree di erent schools of thought are identi ed. e rst school perceives the principle of equality as a matter relating to existing emissions in a given base year. e second sees equality as an issue of all countries being equally e ective in combating emissions. e third school perceives equality as basic equal rights to all the Earth’s resources. All in all, the detection of the underlying and di erent standards of equality provides a deepened understanding of the positions by the EU, China and the US in international climate politics.